2018
DOI: 10.3390/ijms19092701
|View full text |Cite
|
Sign up to set email alerts
|

Can Plasma Rich in Growth Factors Be Safe for Parental Use? A Safety Study in the Canine Model

Abstract: Low invasiveness is the main goal of modern surgery. The use of platelet-rich plasma (PRP) is known to be effective in a variety of applications, such as oral, maxillofacial, orthopedic, dermatologic and cosmetic surgeries. However, a potential ergogenic and carcinogenic effect of PRP derivatives by means of the insulin-like growth factor-1 (IGF-1) pathway has been suggested. Because of this notion, the purpose of this study is to assess the effect of a commercially available PRP-derivative intramuscular injec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Autologous Blood Products are based on their content of supra physiological concentrations of autologous anti-inflammatory mediators and growth factors or cells containing these proteins, leading to a reduction in inflammatory [43][44][45][46]. Autologous Blood Products can reduce pain and lameness scores and increase weight bearing when injected into OA joints [47][48][49], superior to both placebo and hyaluronan in several clinical outcome measures [12,19]. In dogs, studies have shown that Autologous Blood Products can produce improvements up to 12 weeks, with increased activity levels, decreased lameness, and pain [48,50].…”
Section: Discussionmentioning
confidence: 99%
“…Autologous Blood Products are based on their content of supra physiological concentrations of autologous anti-inflammatory mediators and growth factors or cells containing these proteins, leading to a reduction in inflammatory [43][44][45][46]. Autologous Blood Products can reduce pain and lameness scores and increase weight bearing when injected into OA joints [47][48][49], superior to both placebo and hyaluronan in several clinical outcome measures [12,19]. In dogs, studies have shown that Autologous Blood Products can produce improvements up to 12 weeks, with increased activity levels, decreased lameness, and pain [48,50].…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports on different autologous blood products sharing a similar action mode to BCS described a positive effect in OA patients, reducing pain, improving lameness scores, and increasing weight bearing [ 39 , 40 , 41 ]. These results proved to be superior to placebo or hyaluronan in several clinical outcome measures [ 19 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Growth factors affect nearly every biological process [24] and, in platelets concentrates, insulin-like growth factor (IGF-1), transforming growth factor-β (TGF-β), platelet-derived growth factor (PDGF), vascular endothelial growth factor (VEGF) and basic fibroblast growth factor (b-FGF), signal cells to proliferate and influence their maturation, differentiation and tissue repair [25,26]. Growth factors can be obtained from other sources, such as autologous conditioned plasma, and are able to reduce pain and lameness scores, and increase weight bearing when injected into OA joints [27][28][29]. In dogs, a single intra-articular (IA) PRP injection has resulted in clinical improvements for 12 weeks, in some cases without progression of radiographic signs [27,30,31].…”
Section: Introductionmentioning
confidence: 99%